Exaggerated IL-15 and Altered Expression of foxp3+ Cell-Derived Cytokines Contribute to Enhanced Colitis in Nlrp3−/− Mice - Simon A. Hirota; Aito Ueno; Sarah E. Tulk; Helen M. Becker; L. Patrick Schenck; Mireille S. Potentier; Yan Li; Subrata Ghosh; Daniel A. Muruve; Justin A. MacDonald; Paul L. Beck (Hindawi Limited, 2016)
The pathogenesis of Crohn's disease (CD) involves defects in the innate immune system, impairing responses to microbes. Studies have revealed that mutations NLRP3 are associated with CD. We reported previously that Nlrp3−/− mice were more susceptible to colitis and exhibited reduced colonic IL-10 expression. In the current study, we sought to determine how the loss of NLRP3 might be altering the function of regulatory T cells, a major source of IL-10. Colitis was induced in wild-type (WT) and Nlrp3−/− mice by treatment with dextran sulphate sodium (DSS). Lamina propria (LP) cells were assessed by flow cytometry and cytokine expression was assessed. DSS-treated Nlrp3−/− mice exhibited increased numbers of colonic foxp3+ T cells that expressed significantly lower levels of IL-10 but increased IL-17. This was associated with increased expression of colonic IL-15 and increased surface expression of IL-15 on LP dendritic cells. Neutralizing IL-15 in Nlrp3−/− mice attenuated the severity of colitis, decreased the number of colonic foxp3+ cells, and reduced the colonic expression of IL-12p40 and IL-17. These data suggest that the NLRP3 inflammasome can regulate intestinal inflammation through noncanonical mechanisms, providing additional insight as to how NLRP3 variants may contribute to the pathogenesis of CD.